2008
DOI: 10.3758/cabn.8.3.329
|View full text |Cite
|
Sign up to set email alerts
|

It all sounds the same to me: Sequential ERP and behavioral effects during pitch and harmonicity judgments

Abstract: The representation of complex sounds was examined by comparing both behavioral and event-related brain p potentials (ERPs) to the change or repetition of fundamental frequency (ƒ 0 ) and harmonicity. In the pitch task, p participants were asked to categorize the incoming stimulus as either low or high, regardless of harmonicity, f and in the harmonicity task, participants indicated whether the stimulus was tuned or mistuned, regardless of p pitch. Over three experiments, participants were faster in responding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Second, old-plus-new effects on simultaneous ASA have mainly been demonstrated for simple repetition (see also Best et al, 2008; Dyson and Alain, 2008), and have been shown to break down rapidly with more complex forms of predictability (Jones and Litovsky, 2008; Best et al, 2010). In contrast, sequential old-plus-new effects occur with predictable patterns of sound events exceeding mere repetition, as reviewed above.…”
Section: Predictability As a Sequential Analogue To The Simultaneous mentioning
confidence: 99%
“…Second, old-plus-new effects on simultaneous ASA have mainly been demonstrated for simple repetition (see also Best et al, 2008; Dyson and Alain, 2008), and have been shown to break down rapidly with more complex forms of predictability (Jones and Litovsky, 2008; Best et al, 2010). In contrast, sequential old-plus-new effects occur with predictable patterns of sound events exceeding mere repetition, as reviewed above.…”
Section: Predictability As a Sequential Analogue To The Simultaneous mentioning
confidence: 99%